Sosialisasi Safetyriding Pada Siswa Sma Dengan Menggunakan Metode Ceramah Dan Media Audiovisual - Adhinda Putri; Putri Yanti; Musyahidah Mustakim; Tenri Diah T.A; Asna Ampang Allo; Idhar Darlis; Ibnul Aljauzi Amri (Window of Community Dedication Journal, 2024)
Safety and security are the main things that need to be considered when driving on the road, both for four-wheeled and two-wheeled vehicle users. The risk factors for traffic injuries include various aspects, one of which is human error. Teenagers need to be coached and given good guidance to be more careful when driving. The aim of this community service is to increase the knowledge of youth groups regarding safety riding at SMAN 10 Makassar. The method provided in implementing this socialization is in the form of a lecture method and audiovisual media which is divided into 3 stages. Stage 1 preparation includes determining the schedule and preparing educational tools and instruments. Stage 2 of implementation includes a pre-test providing counseling material, a question and answer session and discussion as well as a post-test. Stage 3 is the evaluation stage. The results obtained show that there is an influence of providing lecture and audiovisual method counseling on the knowledge of students at SMAN 10 Makassar with the results of the Wilcpxon Test obtaining a p value (0.001).